HIGH PREVALENCE OF ANXIETY AND 15-YEAR CARDIOVASCULAR RISK IN RUSSIA/SIBERIA INHABITANTS (WHO FRAMEWORK “MONICA-PSYCHOSOCIAL”) - V. V. Gafarov; E. A. Gromova; D. O. Panov; I. V. Gagulin; A. V. Gafarova (Российский кардиологический журнал, 2017)
Aim. To assess the influence of high level of personal anxiety (PA) on the differences in hazard ratios of myocardial infarction development and stroke in men and women in open population of Russia/Siberia.Material and methods. Under the 3rd screening of WHO program “MONICApsychosocial” we investigated random representative selection of inhabitants of Novosibirsk city, age 25-64 year old, in the year 1994 (males n=657, females n=870). The program included registration of social and demographic data, personal anxiety assessment. During 16 years of follow-up novel cases number of myocardial infarction (MI) and strokes reached 15 cases in women 15 and 35; in men 30 and 22, respectively. Statistics was done with SPSS. Criteria χ2 was applied for hazard ratio (HR) calculation — Cox-regression. Significance of all analysis types was set with threshold at p≤0,05.Results. In the open population of 25-64 y.o. PA was assessed in 59,9% of women and 50,9% of men. In monofactory Cox model in 16 years the HR of MI among persons with high PA was higher in women than in men (HR =4,19 and HR =3,7, resp.), and for stroke, reverse, in men higher than in women (HR =4,43 and HR =3,5, resp.). In multifactor Cox model, in persons 55-64 y.o. the influence of high PA on MI risk remained, which was higher in women than in men (HR =5,95, HR = 3,56, resp.). The highest HR for stroke, in high PA, was in divorced (HR =5,017) and widowed men (HR =3,848), at the age 55-64 y.o. (HR =5,8). Among women, there were no such correlations.Conclusion. The prevalence of high PA among inhabitants was 50% higher in women, than in men. Risk of MI development during 16-year timeline was higher in women, and of stroke — in men.